Ethno-genetics of AIM1 gene relating to Human Skin Pigmentation among Six Indigenous Nationalities in Nepal - Singh, Nanda Bahadur (Journal of Institute of Science and Technology, 2015)
This paper attempts to find out allele frequencies of AIM1 gene among six ethnic groups in Nepal by detecting a total number of 456 blood and nail samples through an allele specific PCR amplification. The research findings revealed that the AIM1 codon L374F polymorphism distinctively showed conspicuous ethnic distribution of the two alleles; namely allele “F” was found mostly high (11.4%) in the Caucasoid Chidimar and rarely low (1.1%) in the Dravidian Munda whereas Mongoloid Chepang, Gurung, Raute and Thakali entirely lacked the “F” allele and showed the monomorphic type for the “L” allele. The codon L374F could be the best genetic marker for distinguishing Caucasian populations from Mongoloid ones and would explain the ethno-genomics of human skin coloration among many ethnic groups in the world. Journal of Institute of Science and Technology, 2015, 20(2): 90-93